Six New 9,19-Cycloartane Triterpenoids from Cimicifuga foetida L. - Zhu, Guo-Lei (Nat Prod Bioprospect, 2016)
Six new 9,19-cycloartane triterpene derivatives, as well as 3 known analogues (7–9), were isolated from the roots of Cimicifuga foetida L. Their structures were established on the basis of extensive spectroscopic analyses (IR, UV, ORD, HRESIMS, 1D and 2D NMR). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13659-016-0097-3) contains supplementary material, which is available to authorized users.